Perbedaan kadar gula darah ibu hamil berdasarkan jenis persalinan di Kecamatan Langsa Baro Kota Langsa - Veri, Nora; Aufa, Fachrani; Henniwati, Henniwati; Rizki, Syari Fitri Budia; Syahputra, Anda (Poltekkes Kemenkes Aceh, 2025)
Background: During pregnancy, uncontrolled blood glucose levels can influence the mode and process of delivery. Gestational diabetes may lead to macrosomia due to excessive placental glucose transfer, which is stored as fetal fat. Macrosomia increases the risk of various delivery complications, including cesarean section, preterm birth, neonatal hypoglycemia, and other neonatal complications.Objective: This study aimed to examine differences in maternal blood glucose levels according to the mode of delivery in the working area of Langsa Baro Subdistrict Health Center, Langsa City.Methods: This was an analytic quantitative study with a retrospective design conducted in February 2025 using data from January to December 2024. A total of 119 postpartum women were included using total sampling. Data were obtained from midwives’ medical records at village health posts based on inclusion criteria, entered into a checklist, and analyzed descriptively for univariate data to assess frequency distribution. Bivariate analysis was performed using the independent t-test.Results: The findings showed that the majority of respondents with normal blood glucose levels (60%) delivered spontaneously, whereas 75% of those with abnormal blood glucose levels underwent operative delivery (cesarean section/laparotomy). Statistical analysis indicated a significant difference in maternal blood glucose levels by mode of delivery (p = 0,006).Conclusion: Maternal blood glucose levels differ according to the mode of delivery. Therefore, monitoring and controlling blood glucose levels during pregnancy are essential to prevent maternal and neonatal complications related to pregnancy and childbirth.